Evaluation of anticonvulsant effects of methanolic extract of Olax subscorpioidea Oliv. leaves in chicks and mice - Balarabe Nazif, Abdullahi; Saidi, Odoma; Fatima Ismail, Hassan (J Pharm Bioresour, 2015)
Preparations of Olax subscorpioidea have been used in the Nigerian traditional medicine for the management of convulsions, mental illness, pains, cancer and microbial infections. The efficacy of the leaves of this plant in management of convulsions has been widely acclaimed among the Igala communities of North-Central part of Nigeria and therefore, this study was aimed at examining the anticonvulsant effects of methanolic extract of O. subscorpioidea (MEOS) leaves in order to provide scientific basis for its use in management of convulsions. Phytochemical screening and evaluation of intraperitoneal median lethal dose of the extract was carried out. Anticonvulsant activity of MEOS was evaluated in chicks using maximal electroshock test, and in mice using pentylenetetrazole and strychnine-induced seizure models at doses of 100, 200 and 400 mg/kg. The intraperitoneal median lethal dose of MEOS was estimated to be 3800 mg/kg body weight in mice. MEOS at doses of 100 and 200 mg/kg provided 30 and 70% protection against maximum electroshock induced seizures respectively. The extract also significantly (p < 0.05) increased the mean latency to seizures in a dose dependent manner. MEOS at 100 mg/kg provided 50% protection against strychnine-induced seizures. A significant increase (p < 0.01) and (p < 0.05) in the mean onset of strychnine-induced seizures was also observed with MEOS at doses of 200 and 400 mg/kg respectively. These findings suggest that the methanolic extract of Olax subscorpioidea leaves possess anticonvulsant activity.
Keywords: Anticonvulsant; Maximal Electroshock; Olax subscorpioidea; Pentylenetetrazole; Strychnine